Confirmatory Factor Analysis of the Indonesian University Student Engagement Inventory (USEI) - Erni Agustina Setiowati; Misran Abdullah; Galih Trisurya Nugraha; Tengku R Fitrah At-Taqwa Harahap (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
This study examines the psychometric properties of the Indonesian version of the University Student Engagement Inventory (USEI) among santri university students living in Islamic boarding schools. Using confirmatory factor analysis (CFA), the multidimensional structure of the USEI—comprising behavioral, emotional, and cognitive engagement—was affirmed with satisfactory reliability. The findings align with previous international validations, demonstrating the instrument's applicability within a unique socio-religious context. Notably, affective engagement was more prominent in this population, reflecting the influence of communal and religious environments on student motivation. The study contributes a culturally sensitive tool for measuring student engagement in Indonesian higher education, while acknowledging limitations related to sample generalizability and self-report measures. Future research is recommended to explore longitudinal effects and expand validation across diverse academic settings.